Keunggulan Komparatif Produk Alas Kaki Indonesia Ke Negara ASEAN Tahun 2013 - Silvia Andriani, Kadek Mega; Bendesa, I Komang Gde (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Export of footwear products Indonesia has potential that is strong enough to compete with other countries in ASEAN. The purpose in this research to measure the competitiveness of Indonesia’s footwear products the ASEAN in 2013 and analyze the effect of labor productivity, inflation and exchange rate, the export value of footwear to Indonesia 2000-2013. In this study uses secondary data from 1994-2013 and analyzed using the analysis technique of RCA, RCDA, RTA, ISP, and multiple linear analysis techniques. Results of this study stated that Indonesia has a footwear product comparative advantage decreases, which is analyzed by RCA to measure on the export, import side by RCDA, RTA on side of exports and imports, and ISP’s to measure the stage of growth products footwear, as well multiple linear analysis results for each of the variables that affect labor productivity positively and significantly to the export value of footwear, exchange rate effect is positive but not significant to the export value of footwear, and inflation effect is negative and not significant to the export value of footwear.
Keywords: footwear export; labor productivity; inflation; exchange rates